First Genomic Characterization of blaVIM-1 and mcr-9-Coharbouring Enterobacter hormaechei Isolated from Food of Animal Origin - Mustafa Sadek; Hirofumi Nariya; Toshi Shimamoto; Shizuo Kayama; Liansheng Yu; Junzo Hisatsune; Motoyuki Sugai; Patrice Nordmann; Laurent Poirel; Tadashi Shimamoto (Pathogens, 2020)
We describe here the complete genome sequence of an Enterobacter hormaechei ST279 coharbouring blaVIM-1 and mcr-9 recovered from uncooked beef patty in June 2017, Egypt. The tested isolate was resistant to carbapenem but susceptible to colistin (minimum inhibitory concentration (MIC), 0.5 μg/mL). The antimicrobial susceptibility profile and conjugation experiments were performed. The entire genome was sequenced by the Illumina MiniSeq and Oxford Nanopore methods. The blaVIM-1 and mcr-9 genes are carried on the same IncHI2/pMLST1 plasmid, pMS37a (Size of 270.9 kb). The mcr-9 gene was located within the physical boundaries demarcated by two insertion elements IS903 (upstream) and IS1 (downstream) but did not possess the downstream regulatory genes (qseC/qseB) which regulate the expression of mcr-9. Therefore, the mcr-9 might be silently disseminated among carbapenem-resistant Enterobacterales. In addition to blaVIM-1 and mcr-9, plasmid pMS37a harbored various antibiotic resistance genes including aac(6’)-Il, ΔaadA22, aac(6’)-Ib-cr, sul1, dfrA1 and tetA. To the best of our knowledge, this is the first report of a blaVIM-1 and mcr-9-coharbouring E. hormaechei isolate of food origin worldwide. The identification of a multidrug-resistant VIM-1 and mcr-9 positive Enterobacter hormaechei isolate from food is worrisome as retail meat and meat products could serve as a vehicle for these MDR bacteria, which could be transferred between animals and humans through the food chain. It further highlights that Enterobacterales co-producing MCR and carbapenemases being found in the food chain indeed correspond to a One-Health issue, highlighting the need for serious steps to prevent their further dissemination.